Interactive forms of teaching russian language: student academic and research conference and presentation of scientific project (Eurasian Journal of Philology Science and Education, 2020)
The Relevance of the work is the introduction into the educational process of such interactive forms of learning as a student conference and the presentation of the research project. When creating a training model, professional, general and special competences should be formed. These two forms of interactive learning are aimed at the formation of these competences. The aim of the work is to develop an interdisciplinary strategy for the formation of a system of skills and abilities of independent work of the student. The paper uses the methods of empirical and theoretical research. An important result is the development of professional creative thinking of students. This form of work develops not only academic skills, but also the internal motivation of the student to use interactive forms of learning. As a result of project activities, students must demonstrate the ability to justify the choice of research topics and its relevance; formulate the research topic; determine the goals and objectives of the study; work with various sources of information; analyzereceived information; to compile a Glossary and bibliography in accordance with the requirements for scientific work, as well as to draw up the results of the study in a traditional and creative form.In addition, students master the skills of public speaking at scientific events. Sufficient attention was paid to the formation of criteria for evaluation of the research project and speech at the student scientific conference.